Comprehensive Epitope Analysis of Human Immunodeficiency Virus Type 1 (HIV-1)-Specific T-Cell Responses Directed against the Entire Expressed HIV-1 Genome Demonstrate Broadly Directed Responses, but No Correlation to Viral Load - Addo, M. M. (American Society for Microbiology, 2003)
Cellular immune responses play a critical role in the control of human immunodeficiency virus type 1 (HIV-1); however, the breadth of these responses at the single-epitope level has not been comprehensively assessed. We therefore screened peripheral blood mononuclear cells (PBMC) from 57 individuals at different stages of HIV-1 infection for virus-specific T-cell responses using a matrix of 504 overlapping peptides spanning all expressed HIV-1 proteins in a gamma interferon-enzyme-linked immunospot (Elispot) assay. HIV-1-specific T-cell responses were detectable in all study subjects, with a median of 14 individual epitopic regions targeted per person (range, 2 to 42), and all 14 HIV-1 protein subunits were recognized. HIV-1 p24-Gag and Nef contained the highest epitope density and were also the most frequently recognized HIV-1 proteins. The total magnitude of the HIV-1-specific response ranged from 280 to 25,860 spot-forming cells (SFC)/10(6) PBMC (median, 4,245) among all study participants. However, the number of epitopic regions targeted, the protein subunits recognized, and the total magnitude of HIV-1-specific responses varied significantly among the tested individuals, with the strongest and broadest responses detectable in individuals with untreated chronic HIV-1 infection. Neither the breadth nor the magnitude of the total HIV-1-specific CD8(+)-T-cell responses correlated with plasma viral load. We conclude that a peptide matrix-based Elispot assay allows for rapid, sensitive, specific, and efficient assessment of cellular immune responses directed against the entire expressed HIV-1 genome. These data also suggest that the impact of T-cell responses on control of viral replication cannot be explained by the mere quantification of the magnitude and breadth of the CD8(+)-T-cell response, even if a comprehensive pan-genome screening approach is applied.